The devil may dance : a novel - Tapper, Jake (New York : Little, Brown and Company, 2021)
Charlie and Margaret Marder, political stars in 1960s Washington D.C., arrive in Los Angeles on their latest case, only to be pursued by sinister forces from Hollywood s stages to the newly founded Church of Scientology.
Sequel to The Hellfire Club.
Includes bibliographical references (pages 317-326).
Keywords: Sinatra, Frank -- 1915-1998 -- Fiction; Legislators -- United States -- Fiction; Rat Pack (Entertainers) -- Fiction; Celebrities -- Fiction; Mafia -- Fiction; Murder -- Fiction; Hollywood (Los Angeles. Calif.) -- Fiction; Historical fiction; Political fiction; Thrillers (Fiction)